2022
DOI: 10.3989/scimar.05240.025
|View full text |Cite
|
Sign up to set email alerts
|

Fishery dynamics of blue whiting, Micromesistius poutassou, a highly discarded bycatch species in the NW Mediterranean Sea

Abstract: This study characterized the fishery dynamics of blue whiting, a bycatch species of the bottom trawl Norway lobster fishery, in the NW Mediterranean. Landings and effort data over the last two decades were combined with current information on the spatial distribution of effort and catch, and with the size and age structure of blue whiting over the year. Recruitment to the demersal habitat occurred from 5 cm total length (TL) over the shelf break in spring (April-May), when discards showed the highest values (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Unlike the north Atlantic, where major migrations of blue whiting between feeding areas, in the Norwegian Sea, and the spawning areas west of the British Isles have been reported (Bailey, 1982; Hátún et al, 2007), within the Mediterranean such large‐scale migrations had not been described (Martín et al, 2016). However, recent studies based on the fishery dynamics of the species, showed that the largest individuals only appeared in the catches in winter, their reproductive period, being practically absent during the rest of the year (Mir‐Arguimbau et al, 2022). In light of these observations, the authors suggested migration movements of large individuals from offshore waters to the upper slope (between 200 and 600 m) for reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the north Atlantic, where major migrations of blue whiting between feeding areas, in the Norwegian Sea, and the spawning areas west of the British Isles have been reported (Bailey, 1982; Hátún et al, 2007), within the Mediterranean such large‐scale migrations had not been described (Martín et al, 2016). However, recent studies based on the fishery dynamics of the species, showed that the largest individuals only appeared in the catches in winter, their reproductive period, being practically absent during the rest of the year (Mir‐Arguimbau et al, 2022). In light of these observations, the authors suggested migration movements of large individuals from offshore waters to the upper slope (between 200 and 600 m) for reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Blue whiting larvae at more advanced developmental stages were found close to the coast, in the more productive shelf waters and near the recruitment zones that are located over the shelf (Mir‐Arguimbau et al, 2022). Interestingly, they were mainly located in the canyons head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the adaptive phenotypic plasticity may determine changes in population life history traits even on a short-term scale, depending on the environmental context (Hidalgo et al, 2014). Such natural oscillations occur not only in biological parameters but also in abundance as a result of environmental variations and fishing exploitation (Martin et al, 2016;Mir-Arguimbau et al, 2022). Another limitation of this study is represented by the small sample size of the 1985-86 sample (not fully representative of the population) and the different methodologies used in the two periods.…”
Section: Historical Comparisonmentioning
confidence: 96%
“…Another limitation of this study is represented by the small sample size of the 1985-86 sample (not fully representative of the population) and the different methodologies used in the two periods. The different selectivity of the net due to different mesh sizes represents a limit to properly compare the LFDs and size structure of the samples, even if we can assume a comparable selectivity on adult specimens since it was reported that juveniles smaller than 20 cm TL account for a large proportion of catches in otter bottom trawler deploying a 40 mm mesh size at the codend (Mir-Arguimbau et al, 2022).…”
Section: Historical Comparisonmentioning
confidence: 99%